ANALISIS PERSEBARAN KESESUAIAN INSTALASI PHOTOVOLTAIC PADA BANGUNAN KAMPUS PUSAT UNIVERSITAS NEGERI PADANG - Usqo Irwanto (JURNAL BUANA, 2022)
The purpose of this research is to find out the roof of Padang States University (UNP) Central Campus building that is suitable for photovoltaic installation on UNP central campus, West Air Tawar, Padang with several criteria for conformity of PV installation in the scope of spatial science. This type of research is quantitative. The data used in this study are insolation data in 2019, DEMNAS, building shapefiles, and building height data. The analysis used is Elevation Pixel Manipulation to obtain total building elevation, Solar Radiation Area to obtain insolation data received by the roof of the building, and conditional criteria of roofing buildings suitable for PV. The results of this study showed from 81,652.71 m2 roof area of buildings spread across various faculties (including graduate buildings), 81,080.65 m2 which is indicated suitable for PV installations, and amounted to 572.06 m2 or 0.7 percent of the total building roof area due to having insolation of less than 800 kWh/m2 and a total area of less than 30 m2.